Electrical power systems quality - Dugan, Roger C.; McGranaghan, M. F.; Santoso, Surya; Beaty, H. Wayne (McGraw Hill, 2012)
A guide to identifying and preventing the causes of power quality problems. This resource addresses the essentials of power quality and tested methods used to improve compatibility among the power systems, customer equipment, and processes.